2015
DOI: 10.1155/2015/320941
|View full text |Cite
|
Sign up to set email alerts
|

Blood Brain Barrier: A Challenge for Effectual Therapy of Brain Tumors

Abstract: Brain tumors are one of the most formidable diseases of mankind. They have only a fair to poor prognosis and high relapse rate. One of the major causes of extreme difficulty in brain tumor treatment is the presence of blood brain barrier (BBB). BBB comprises different molecular components and transport systems, which in turn create efflux machinery or hindrance for the entry of several drugs in brain. Thus, along with the conventional techniques, successful modification of drug delivery and novel therapeutic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
171
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(171 citation statements)
references
References 240 publications
(196 reference statements)
0
171
0
Order By: Relevance
“…In GBM, a disruption of BBB by the primary tumor sites is often observed [35]. This altered BBB allows passive accumulation of chemotherapeutic drugs in the vicinity of the disruption [36]. However, the degree of BBB disruption varies depending on the region of the GBM tumors and may be negligible for certain tumors.…”
Section: Crossing the Bbb: A Challenge For Gbm Therapymentioning
confidence: 99%
“…In GBM, a disruption of BBB by the primary tumor sites is often observed [35]. This altered BBB allows passive accumulation of chemotherapeutic drugs in the vicinity of the disruption [36]. However, the degree of BBB disruption varies depending on the region of the GBM tumors and may be negligible for certain tumors.…”
Section: Crossing the Bbb: A Challenge For Gbm Therapymentioning
confidence: 99%
“…The efflux and influx transporters of BBB comprise transporters like ATP-binding cassette transporters and solute carrier transporters. [12] The different types of transport across the BBB are shown in Figure 1 The inability of drugs to cross the BBB is one of the major impairments to developing treatments for neurological diseases. [13][14][15][16] This highly restrictive, physiologic barrier prevents 98% of small-molecule drugs and virtually 100% of large-molecule drugs from reaching the central nervous system from blood circulation.…”
Section: Ideal Properties Of Nanoparticles For Drug Deliverymentioning
confidence: 99%
“…Possible advantages of nanoparticle delivery systems over conventional anticancer chemotherapy include: (i) protection of drugs from degradation in the body; (ii) enhanced absorption into tumor cells; and (iii) decreased interaction of drugs with normal cells. [8] Ideal properties of nanoparticles for drug delivery are shown in Table 1. Nano-based drug delivery carriers, or nanocarriers, can consist of a wide variety of materials, both organic (polymeric, lipid, protein, or viral) and inorganic.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of intact BTB in these regions of tumors considerably impedes drug delivery from the blood to the tumor tissue, leading to a high recurrence rate after chemotherapy. 3 A host of animal studies in recent years have demonstrated that in the presence of circulating microbubbles (MBs), focused ultrasound (FUS) at low acoustic pressures could be used to open the blood-brain barrier (BBB) of normal brains locally, noninvasively and reversibly. [4][5][6][7][8][9] Studies performed on nonhuman primates have revealed that BBB opening could be realized by FUS exposure with MBs through the intact skull.…”
Section: Introductionmentioning
confidence: 99%